Theoretical Simulation Study on Controlling Factors in Horizontal Well CO2 Stimulation of Heavy Oil. (21st July 2014) - Liu, Tongjing; Diwu, Pengxiang; Jiang, Baoyi; Jiang, Liwu; Liu, Rui
Abstract : Since CO2 Stimulation in Horizontal Wells can avoid the problem of steam flooding, clay swelling, and sand production, it has been carried out in many fields. To improve the research on the controlling factors and their influence and establish a specific reservoir selecting method, this paper founded the components and geology model according to typical heavy oil reservoirs firstly. Comparing with pilot test, the theoretical model result could give expression to the characteristic of large water ratio descend rang, long period of validity, and high rounds effectiveness. Secondly, this study designed simulation scheme including factors of geology, development, and stimulation technology, to filter the controlling factors of the oil incremental and well reopened water cut and describe their influence. Based on it, we proposed a quick filter criterion to choose heavy oil reservoirs for CO2 stimulation.